The relationship between Corporate Social Responsibility Performance and Corporate Financial Performance: An Empirical Analysis on Chinese listed manufacturing and non-manufacturing companies. - Zhong, Xinyu (2018)
Many companies have focused on corporate social responsibility for a long time. However, corporate social responsibility, as a controversial topic, has been debate for decade years, the most controversial issue of corporate social responsibility is the relationship between corporate social responsibility and the corporate financial performance. Many researches have studied this issue based on the Western countries. This paper explores and tests whether the corporate social responsibility performance has a positive impact on corporate financial performance in China. Data of 120 Chinese listed manufacturing companies and 120 Chinese listed non-manufacturing companies from 2012 to 2016 are used to do the quantitative research. The relationship is tested by panel regression analysis. The corporate social responsibility is evaluated by Hexun website and the corporate financial performance is measured by gross profit margin, return on assets and return on equity in this paper. The result indicates that CSR performance has a positive impact on CFP. When CSR performance increases, CFP will increase with it.